Exploring the casual association between coffee intake and bladder cancer risk using Mendelian Randomization - Deng, Yuqing; Wu, Tingting; Luo, Gang; Chen, Lin (Frontiers in Genetics, 2022)
Objective Several observational studies have suggested that coffee consumption is associated with a lower risk of bladder cancer. However, observational studies are susceptible to confounding factors and reverse causality. We used a two-sample Mendelian randomization (MR) method to assess the causal nature of this association. Methods At the genome-wide significance level (P<5×10-8), 12 single nucleotide polymorphisms (SNPs) strongly associated with coffee consumption were used as instrumental variables (IVs). Summary-level data on genetic variation in bladder cancer were obtained from the UK biobank (420,838 samples) and FinnGen consortium (175,121 samples). Multiple MR methods were used. Heterogeneity and horizontal pleiotropy were detected using Cochran's Q test and MR-Egger. Results Twelve SNPs were included in the primary analysis. After excluding 8 SNPs with potential secondary phenotypes, the remaining 4 SNPs were included in the sensitivity analysis. In all analyses, Cochran’s Q statistic indicated that there was no heterogeneity among SNPs, and the MR-Egger analysis did not reveal the existence of horizontal pleiotropy (P>0.05). In the UK Biobank, the odds ratio (OR) for bladder cancer was 1.022 (95% confidence interval (CI), 0.679-1.537) for per 50% increase in coffee consumption. Consistent results were obtained in the FinnGen consortium (OR=0.890, 95% CI, 0.467-1.697). Sensitivity analysis showed consistent results with primary analysis. Conclusion This study does not support a causal association between habitual coffee consumption and bladder cancer risk.